The Impact of Multicultural Awareness, Social Practices, and Gender Equality on Community Solidarity through Humanistic Values in Private Universities - Setiadi, Hedi; Ambiapuri, Ema; Parwitasari, Nur Aini; Wiyono, Darul (Jayapangus Press, 2025)
In private higher education institutions (PHEIs) with various cultural, social, and gender diversity, community solidarity is a significant aspect of developing a harmonious and productive working atmosphere. The aim of this study is to explore how multicultural awareness, social practices, and gender equality influence community solidarity through humanistic values among administrative staff at PHEIs in Bandung. The study is quantitative in nature, using self-administered questionnaires as primary data. This research is descriptive quantitative with a purposive sampling method and a population of 500 administrative staff in PHEIs in Bandung City. A margin of error of 5% with the Slovin formula was used to determine the sample size, which was 223 respondents representing the population. Such data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS 3.0 statistical application. Findings indicate that multicultural awareness, social practices, and gender equality had a significant direct positive effect on community solidarity. Also, humanistic values act as a partial mediator of these relationships, reinforcing the effect of three independent variables on community solidarity. Building an inclusive, collaborative, and trusting community solidarity requires fostering humanistic values, such as respect for human dignity or social responsibility. This study concludes that policies that support multicultural awareness, active social practices, and gender equality can improve community solidarity in each PHEI in Bandung City. The results offer practical implications for PHEI administrators in developing a more harmonious workplace and add to the academic literature on the significance of humanistic values as a partial mediator of the relationships of variables.